Good to great why some companies make the leap--and others don't - Collins, James C ([New York] HarperCollins, 2011)
Answers to commonly asked questions about how good-to-great principles can help social sector organizations make the leap to greatness, using interviews with over 100 social sector leaders
2
Keywords: Leadership; Organizational change; Strategic planning